Kajian Keberlanjutan Permukiman Nelayan di Kampung Tanjungsari, Kabupaten Pemalang - Purwoningsih, Purwoningsih (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Tanjungsari village is one of the fishing settlement located in Pemalang. Settlements located in coastal areas is certainly has a wide range of environmental issues concerning environmental, social and economic mutually influence each other. On the one hand, the fishing settlement is one of the potential that exists in Pemalang. If the problem is left unchecked then, a fishing village will be subject to environmental degradation and unsustainable. Therefore, there should be a study that aimed to assess the sustainability of fishing and explain the causes of the research results. The method used in this research is mix method there is a merger between qualitative and quantitative methods. The analysis technique used is quantitative descriptive analysis, qualitative descriptive analysis and scoring analysis. The results of this study is to note that at this time Kampung Nelayan Tanjungsari under moderate conditions on the environmental aspects of physical settlements and coastal areas (value 2.1), bad conditions on aspects of fisheries resource management (score 1.3) and bad conditions in the social and cultural aspects of society (value 1.6). While overall, Kampung Nelayan Tanjungsari included in the category of Sustainability Not in all aspects, as well as the main factor is a factor Economic Sector Fisheries.